Regulation of physiological processes by microRNAs in insects. - Lucas, K.J.; Zhao, B.; Liu, S.; Raikhel, A.S. (Current opinion in insect science, 2015)
MicroRNAs (miRNAs) are small non-coding RNAs that function in gene regulatory processes in plants and animals by targeting sites within messenger RNA. In insects, miRNAs have been shown to regulate a variety of physiological processes throughout insect development, including molting, metamorphosis, oogenesis, embryogenesis, behavior and host-pathogen interactions. The roles of miRNAs in the model organism, Drosophila melanogaster, have been studied extensively due to the conserved nature of miRNA function among highly divergent species. However, seeking to understand miRNA function in non-drosophilid insect species has become a growing trend in insect science. Here, we highlight the recent discoveries regarding miRNA function in insect physiology and development.